Governance arrangements and adaptive decision-making in rice farming systems in Northern Ghana. (1st November 2018) - Nyamekye, Andy Bonaventure; Dewulf, Art; Van Slobbe, Erik; Termeer, Katrien; Pinto, Cristina
Abstract: Climate variability has consequences on water availability in rice farming systems. In Ghana, rice farmers in the Northern Savannah are amongst the most vulnerable to long periods of drought and erratic rainfall conditions. Within the Kumbungu district, farmers engaged in both rain-fed and irrigated rice farming are no exception. Coping with uncertain water availability conditions requires adaptive decision-making for sustained productivity in rice cropping. From an adaptive governance perspective, the extent to which formal and traditional governance arrangements enable adaptive decisions amongst rice farmers remains a key question. Using an exploratory research design, the study investigates three key questions; what water-dependent decisions rice farmers take and how these are adaptive to changing water availability conditions; what formal and informal governance arrangements rice cropping decisions are embedded in; and how existing governance arrangements enable or constrain adaptive decision-making. Rice farmers in twelve communities around the Bontanga Irrigation Scheme in the Kumbungu District in the Northern region were engaged through individual interviews and focus group discussions. The study reveals that farmers take six major water-dependent decisions throughout the cropping season; decision to or not to plant rice, land preparation, planting, weed control, fertilizer application and harvesting. Farmer decisions are most adaptive to water availability conditions during planting and fertilizer application. Both formal and traditional governance arrangements influence the extent to which farmers are able to adapt to changes in water availability conditions. The paper also reflects on the potential of hydro-climatic information and the place of Environmental Virtual Observatories (EVOs) in adaptive governance and decision-making.